Coatings for SOFC Interconnects in Fuel Side Environments. (2nd June 2015) - Sachitanand, Rakshith; Sattari, Mohammad; Svensson, Jan-Erik; Froitzheim, Jan
Abstract : This study focuses on examining the effect of PVD coatings on the oxidation performance of interconnects in fuel side environments. The ferritic steels Sanergy HT and AISI 441 were coated with nanoscale thick rare earth oxides of Ce and La. Additionally, Sanergy HT was also coated with Cu, Co and Ce/Co .The samples were exposed at 850°C in Ar-5 %H2-3% H2O in a tubular furnace. Chemical analysis on the samples was subsequently performed with SEM/EDX and XRD. It was established that the Ce and La coatings brought about a ≈4x reduction in the oxidation rate while the Cu and Co coatings remained metallic and negatively affected oxidation performance. Additionally, reaction of the La coating with the thermally grown oxide resulted in the formation of a perovskite phase which could be further developed to improve the electronic properties of the oxide.